PROTECTION OF THE CIVILIAN POPULATION IN CONDITIONS OF MARTIAL LAW - Шутяк, Ірина; Іншеков, Михайло; Євтушок, Володимир (SWorldJournal, 2023)
The work considers the concept of martial law. The topicality of the topic is due to the fact that the norms that regulate the problem of protecting the civilian population, as a vulnerable category, are contained in various international treaties and mos